Efficacy of bone cement volume in unilateral kyphoplasty of thoracolumbar compression fractures: A clinical comparative study - Hüseyin Berk Benek; Tahsin Ulgen; Alper Tabanlı; Cafer Ak; Emrah Akcay; Hakan Yilmaz (Acta Orthopaedica et Traumatologica Turcica, 2025)
Objective: To compare the clinical and radiological e!cacy of bone cement volumes injected during unilateral percutaneous balloon kyphoplasty for thoracolumbar vertebral compression fractures.